2008
DOI: 10.1038/ismej.2008.72
|View full text |Cite
|
Sign up to set email alerts
|

Presence and activity of anaerobic ammonium-oxidizing bacteria at deep-sea hydrothermal vents

Abstract: Recent studies indicate that ammonia is an important electron donor for the oxidation of fixed nitrogen, both in the marine water column and sediments. This process, known as anammox, has so far only been observed in a large range of temperature habitats. The present study investigated the role of anammox in hydrothermal settings. During three oceanographic expeditions to the MidAtlantic Ridge, hydrothermal samples were collected from five vent sites, at depths ranging from 750 to 3650 m from cold to hot habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 36 publications
4
113
0
Order By: Relevance
“…Later, studies of oxygen minimum zones showed the presence of anammox bacteria in the Arabian Sea and the Benguela and Peru upwelling zones (6,12,22,23). Furthermore, the anammox process has been detected at high temperatures in deep-sea hydrothermal vents on the Mid-Atlantic Ridge (3). These studies indicated that denitrification is not the only process playing a role in the loss of fixed nitrogen (1).…”
mentioning
confidence: 89%
“…Later, studies of oxygen minimum zones showed the presence of anammox bacteria in the Arabian Sea and the Benguela and Peru upwelling zones (6,12,22,23). Furthermore, the anammox process has been detected at high temperatures in deep-sea hydrothermal vents on the Mid-Atlantic Ridge (3). These studies indicated that denitrification is not the only process playing a role in the loss of fixed nitrogen (1).…”
mentioning
confidence: 89%
“…For example, in the permanently cold sediment of Young Sound, Greenland, with a temperature of <1°C year round, the temperature optimum for anammox was 12°C , and in the Skagerrak, with annual temperatures between 4°C and 6°C, the optimum temperature was 15°C . Recently, anammox activity, ladderane lipids, and 16S rRNA genes were observed at hydrothermal vents and in hot springs which have expanded the temperature ranges significantly (Jaeschke et al 2009b;Byrne et al 2009). The wide range in growth temperature of anammox bacteria may promote their existence in wetlands.…”
Section: Temperaturementioning
confidence: 99%
“…The anammox process has been demonstrated in marine ecosystems (15,19,20,31,43,45,47) and freshwater terrestrial ecosystems (29,41), low-temperature polar regions (32,33) and high-temperature hot spring and deep sea hydrothermal vents (3,13), and oil reservoirs (22), even on the surface of marine sponges (12,26). Certain Planctomycetes are monophyletic members linked to this process, and five genera, 'Candidatus Brocadia', 'Candidatus Kuenenia', 'Candidatus Anammoxoglobus', 'Candidatus Scalindua' and 'Candidatus Jettenia', have been described (16-18, 30, 37).…”
mentioning
confidence: 99%